2023
DOI: 10.1101/2023.01.18.524509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amplitude modulation pattern of rat distress vocalisations during fear conditioning

Abstract: In humans, screams have strong amplitude modulations (AM) at 30 to 150 Hz. These AM correspond to the acoustic correlate of perceptual roughness. In bats, distress calls can carry AMs, which elicit heart rate increases in playback experiments. Whether amplitude modulation occurs in fearful vocalisations of other animal species beyond humans and bats remains unknown. Here we analysed the AM pattern of rat's 22-kHz ultrasonic vocalisations emitted in a fear conditioning task. We found that the number of vocalisa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Such reduction could potentially be attributed to fatigue (as observed in humans, Kitch and Oates, 1994), despair (e.g., as a reaction to the lack of effects from repeated emissions of 22-kHz calls), or both. The reduction in the amplitude of 22-kHz calls during the 10-trial fear conditioning was also recently observed by others (Gonzalez-Palomares et al, 2023).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Such reduction could potentially be attributed to fatigue (as observed in humans, Kitch and Oates, 1994), despair (e.g., as a reaction to the lack of effects from repeated emissions of 22-kHz calls), or both. The reduction in the amplitude of 22-kHz calls during the 10-trial fear conditioning was also recently observed by others (Gonzalez-Palomares et al, 2023).…”
Section: Discussionsupporting
confidence: 83%
“…In a recent publication during this paper's review process, Gonzalez-Palomares et al (2023), inspired by our current findings, investigated and reported 44-kHz vocalizations following prolonged (10-trial procedure) odor fear conditioning. These calls were observed predominantly during the late ITI, i.e., 8 th -10 th ITI (Gonzalez-Palomares et al, 2023;Fig. S4C; please note 4 th -7 th ITI were not investigated) after the shock presentations (Fig.…”
Section: -Khz Calls In Long Aversive Stimulationmentioning
confidence: 92%